Pelatihan Pengetahuan Umum Perbankan bagi Rekrutmen Baru Divisi Pemasaran Bank ABC - Andreas Murti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Proper recruitment in the banking sector, particularly for marketing positions, is crucial in facing intense competition and evolving customer demands. Professional and competent marketing personnel are able not only to attract new customers but also to build long-term relationships that directly impact business growth and sustainability. Training for new employees in the marketing field is crucial to equip them with product understanding, communication skills, and service ethics in accordance with banking industry standards, so they can carry out their roles effectively and contribute to achieving the bank's business targets. Marketing personnel need to be equipped with general banking knowledge, including funding products, credit or financing products, payment systems, foreign exchange transactions, trade finance transactions, and how banks worldwide communicate through the Society for Worldwide Interbank Financial Telecommunication (SWIFT) system.